HPA axis function in male caregivers: effect of the monoamine oxidase-A gene promoter (MAOA-uVNTR) - Brummett, Beverly H. (2008)
Caregiving stress is associated with negative health outcomes. Neuroendocrine functioning may be a mediator of such outcomes. The MAOA gene regulates activity of neurotransmitters involved with neuroendocrine responses to stress. Differences in polymorphisms of this gene have been shown to influence susceptibility to stress. Therefore, we examined allelic variation in MAOA-uVNTR, a functional polymorphism of MAOA, as a moderator of chronic stress effects on urinary cortisol excretion in 74 males enrolled in a case/control study of caregivers for relatives with dementia. Mixed models analysis of variance were used to examine MAOA-uVNTR genotype (3 vs 3.5/4 repeats) as a moderator of the impact of stress (caregiver versus non-caregiver) on the urinary excretion pattern (overnight, daytime, evening) of cortisol. Caregivers with MAOA-uVNTR alleles associated with less transcriptional activity (3-repeats) displayed a pattern of cortisol excretion–a decrease from overnight to daytime—that was suggestive of HPA axis blunting, as compared to noncaregivers and those caregivers with the more active alleles (3.5/4 repeats) (cortisol p<.043). Individuals with less active MAOA-uVNTR alleles who are under chronic stress may be at increased risk for exhaustion of the HPA response to such stress.